Synthesis, Characterization of Polyvinyl Alcohol-Chitosan-ZnO/CuO Nanoparticles Film and Its Biological Evaluation as An Antibacterial Agent of Staphylococcus aureus - Fatoni, Ahmad; Hasanah, Mauizatul; Sirumapea, Lasmaryna; Putri, Annisa Defanie; Sari, Khoirunnisa; Khairani, Restu Dwi; Hidayati, Nurlisa (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2023)
The polyvinyl alcohol-chitosan-ZnO/CuO nanoparticles film was researched. Synthesis, characterization, and its biological evaluation as an antibacterial of Staphylococcus aureus were the aims of this research. The biosynthesis of ZnO, CuO, and ZnO/CuO nanoparticles was done using the biological method. The polyvinyl alcohol-chitosan-ZnO/CuO nanoparticles film was synthesized using the casting method. All the products were characterized by FTIR spectroscopy, X-ray diffraction, and Scanning Electron Microscope (SEM). Polyvinyl alcohol-chitosan-ZnO/CuO nanoparticles film as a paper disk for the evaluation as an antibacterial agent through the agar disk diffusion method. The absorption bands of ZnO, CuO, and ZnO/CuO nanoparticles can be observed at 318, 274, and 252 nm, respectively. The peaks at wavenumbers 433-673 and 619 cm-1 were Zn-O and Cu-O groups, respectively. The Zn-O and Cu-O groups at ZnO/CuO nanoparticles can be observed at 474 and 619 cm-1. The appearance of Zn-O and Cu-O groups at film PVA-chitosan-ZnO/CuO nanoparticles indicates the wavenumber between 433 and 673 cm-1. The physical structure of ZnO, CuO, and ZnO/CuO nanoparticles is crystalline form. The crystallite size of ZnO, CuO, and ZnO/CuO nanoparticles was estimated at 1.0572, 6.6315, and 2.3333 nm respectively. The physical structure of film PVA-chitosan-ZnO/CuO nanoparticles is amorphous. The surface morphology of films C, D, and E was affected by the addition of chitosan and ZnO/CuO nanoparticles. The film of PVA-chitosan-ZnO/CuO nanoparticles (C, D and E) can act as an antibaterial agent of Staphylococcus aureus.The inhibition zone of film D is higher than A, B, C, and E.